Preloved Shopping - Efrianti Efrianti; Nurul Ilmi Idrus (Universitas Muslim Maros, 2020)
Online shopping has become part of public shopping activities, through social media such as Facebook, Instagram, etc., with various shopping convenience. Since the rise of online businesses, Instagram is one of the most popular shopping media, both for new and preloved goods. While a number of existing literatures concentrate on online shopping with various new items, little if any deals with preloved shopping with specific items, focusing on its management. This article fills this gap. This study was conducted on social media Instagram on preloved goods seller accounts through which preloved goods are sold. The informants in this study were female sellers and buyers of preloved goods, as they are the dominant preloved sellers and buyers, particularly cosmetics and fashion. There were 11 women participated in this study, they are varied based on age (between 19 and 25 years), occupation (six female students, a celebgram, entrepreneur, influencer, and barista respectively), and status (six buyers and five owners who at the same time act as administration staff (admin). The study indicates that cosmetics and fashions are two types of preloved item which are popularly sold and bought in Instagram. Although used goods are very diverse, the term preloved is used limitedly, and used products such as cosmetics and fashion are included as preloved items. Among other preloved items in Instagram, cosmetics (such as make up and skin care) and fashion (such as bags, shoes, assesories, clothes) are the most popular items. Reduced price (“harga miring”), brand (merek), and trying out (coba-coba) are three main reasons why women buy preloved cosmetics; while brand (merek), style (model), reduced price (“harga miring”), and quality are four main reasons why preloved fashion are bought. In addition, brands and